2009
DOI: 10.1179/136217109x12518083193559
|View full text |Cite
|
Sign up to set email alerts
|

Tool design and stir zone grain size in AZ31 friction stir spot welds

Abstract: The influence of tool design and tool rotational speed variations on the torque, energy output, stir zone temperature and average grain size in the stir zones of AZ31 friction stir spot welds was investigated. The average stir zone grain size decreased by y1 mm in AZ31 friction stir spot welds made using a three-flat/threaded tool design and tool rotational speeds of 2250 and 3000 rev min 21 . However, there was no statistically significant influence of tool design on the average grain sizes in friction stir s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Unlike the Mg 17 Al 12 intermetallic that would completely melt at equilibrium at 437 °C, Al 8 Mn 5 phase will begin melting at equilibrium only at 989 °C as it is more thermodynamically stable . The maximum temperature measured during friction stir spot welding of AZ31 using a rotational speed of 3000 rev/min was estimated to be 580 °C, which is well below the melting temperature of Al 8 Mn 5 intermetallics . This argument can be extended to all types of Al–Mn phases that could be present in the alloy, since even Al 6 Mn, the least thermodynamically stable phase, will remain solid up to 658 °C .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Unlike the Mg 17 Al 12 intermetallic that would completely melt at equilibrium at 437 °C, Al 8 Mn 5 phase will begin melting at equilibrium only at 989 °C as it is more thermodynamically stable . The maximum temperature measured during friction stir spot welding of AZ31 using a rotational speed of 3000 rev/min was estimated to be 580 °C, which is well below the melting temperature of Al 8 Mn 5 intermetallics . This argument can be extended to all types of Al–Mn phases that could be present in the alloy, since even Al 6 Mn, the least thermodynamically stable phase, will remain solid up to 658 °C .…”
Section: Resultsmentioning
confidence: 83%
“…FSSW is a promising technique that can allow the utilization of magnesium alloys in the automotive sector. As a result, significant attention was given to both corrosion and welding of magnesium alloys separately, but the combination of both is a field yet to be well understood . Previous studies have shown the SZ to be noble to the base metal, and produce a local galvanic cell that resulted in the accelerated corrosion of the TMAZ region .…”
Section: Introductionmentioning
confidence: 99%
“…The microstructural evolution during the welding process results in the formation of three major regions in completed joints: the stir zone (SZ), thermo‐mechanically affected zone (TMAZ), and heat affected zone (HAZ). Both FSSW and corrosion of magnesium alloys have been studied at length; however, the effect of microstructural evolution during the welding process on the corrosion behavior of the joint is still not fully understood .…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in failure load as a function of tool rotation rate can be attributed to the size and microstructure of stir zone as well as the hook features of the faying surface. It has been well-documented in FSSW of similar alloys that the tool rotation rate and tool shoulder plunge depth influence the hooking geometry and microstructure which in-turn affect the mechanical properties [12,15,24,[26][27][28]. Since in stage I the identification of the ideal tool rotation is the primary goal, the influence of the tool rotation rate on mechanical properties of welds will be discussed.…”
Section: Resultsmentioning
confidence: 99%
“…While the tool shoulder predominantly determines the frictional heat generated, the probe pin influences the material flow and mixing during the FSSW [6,12,25,27]. Increasing the tool rotation rate introduces higher frictional heat [16,33,34] and strain rate [33,34] in the weld nugget.…”
Section: Influence Of Tool Rotation Rate On Mechanical Property and Mmentioning
confidence: 99%